Neurovegetative Syndromes in Dentistry - Doroshenko О.; Zozulya І.; Volosovets А.; Savychuk А.; Trostyansky Я. (Actual Dentistry, 2025)
Abstract. The lecture describes the central neurovegetative disorders that occur in the human body due to diseases of the autonomic nervous system, as well as neurovegetative syndromes that accompany various diseases, particularly in neurodentistry. The data will help neurologists and dentists diagnose diseases promptly, provide targeted emergency care, and, to a greater extent, treat them effectively. The lecture focuses on the clinical characteristics of neurovegetative symptoms and syndromes. Under the name “neurovegetative,” we refer to symptoms and syndromes of the autonomic nervous system (central or peripheral parts), which include nuclei or conductive pathways, vegetative structures of internal organs, head, blood vessels, and neuromuscular apparatus.